Myxoid Neurothekeoma: A Rare Soft Tissue Tumor of Hand in a Male Toddler - Akhtar, Kafil (Medknow Publications & Media Pvt Ltd, 2013)
Neurothekeomas are rare benign neoplasms, typically occurring in young patients with a remarkable predilection for the female population. Patients usually present with a small nodule in different anatomical sites, commonly involving the face and the upper limb. We report a case of a three-year-old boy, who presented with a nontender nodule on the left thumb. Surgical biopsy and immunostaining confirmed the diagnosis as myxoid neurothekeoma. The rarity of this unusual skin tumor in a toddler prompted the following report.